Carbon nanotubes and catalysis: the many facets of a successful marriage. Issue 8 (21st August 2015) - Melchionna, M.; Marchesan, S.; Prato, M.; Fornasiero, P.
<x xml:space="preserve">Abstract</x> Carbon nanotubes have emerged as unique carbon allotropes that bear very interesting prospects in catalysis.